A Review of Key Factors on Geosynthetic Clay Liners’ Performance as Liner System - Budihardjo, Mochamad; Chegenizadeh, Amin; Nikraz, Hamid (Planetary Scientific Research Centre, 2012)
Geosynthetic clay liners (GCLs) as a substitute material to compacted clay liner (CCLs) can be employed as landfill leachate barriers, waste water impoundments and any other liquid impediments. They have some advantages in their shape, availability, easy in installation and mainly hydraulic performance. However, the hydraulic performance of GCLs as liquid barricade depends on some factors. In this paper, a review of some key factors that affected the GCLs performance as leachate and liquid barrier will be presented and discussed in order to provide a critical view of GCLs behavior.